Cechy kosmopolityzmu w językowych obrazach świata: Studium porównawcze - Navicka, Tatiana (Investigationes Linguisticae, 2007)
The subject of this article is the meaningful concept of cosmopolitism / cosmopolitanism. While researching its properties, the following questions regarding its uses across the selected languages have been considered in order to obtain a suitable answer: 1) which image of cosmopolitism / cosmopolitanism are proposed both by the nowadays available postcomunist monolingual dictionaries from the Polish, Russian and Latvian areas, and by Western (English) monolingual dictionaries; 2) which image of cosmopolitism / cosmopolitanism seems to be the most proper one for several groups of students living in postcomunist countries (Poland, Russia & Latvia); 3) does the selected dictionary postulates reflect the conceptions belonging to the inquired students or appearing in press articles? The accurate analysing of inquiries and lexicographic staff shows that the image of cosmopolitism in postcomunist countries differs from its image in English areas. As for that, the consideration of cosmopolitanism by Polish, Russian and Latvian students usually does not correspond with the opinion expressed by lexicographers in the definition of this lexem.